“NOOR-2013” A BOLD SEEDED AND HIGH YIELDING CHICKPEA KABULI VARIETY DEVELOPED INDIGENOUSLY - M. Naveed; 2; M. Shafiq; M. Nadeem; A. U. Haq; M. A. Zahid (Journal of Animal and Plant Sciences, 2020)
The evolution of new crop varieties with desirable traits is a continuous process. A crop variety becomes susceptible to various biotic and abiotic plant stresses with the passage of time, thus, necessitating replacement by genotypes possessing better productivity potential and inbuilt tolerance against different stresses. In this perspective, this article reports the progress of a new chickpea kabuli variety “Noor-2013” developed through conventional plant breeding techniques and possesses improved yield potential, extra bold seed size and ability to tolerate different diseases. In 1999-00, two local genotypes, K-96033 (female parent) and K-92029 (male parent) were crossed to create genetic variability for grain size by selecting high yielding recombinants with bold grains. For this purpose, from filial generation one (F1) seed, an F2 population was raised and 299 single plant selections (SPS) were made which were advanced to subsequent generations (F3 to F5) over the years in plant-to-row progenies using the pedigree method of plant selection. Only high yielding recombinants with bold grains were advanced to the next generations. Finally, a promising uniform line “K-60062” later named as “Noor-2013” with pedigree C.19/19/19/109/148/161/62 was selected from F6 recombinants during 2005-06. Later, this line was evaluated for yield potential, and disease reaction during 2006-2013. On an average in different yield trials (station, adaptation and national), this strain produced 32.3% higher yield in comparison to check varieties/standards (Punjab-Noor, CM-2008, CM-2000 and Noor-91). In this process, the candidate variety “Noor-13” achieved a potential yield of 3282 kg ha-1 in national uniform yield trials (NUYTs) during 2010-11 conducted at Arid Zone Research Institute (AZRI), Bhakkar, Punjab, Pakistan. The grains of this new variety is beige in colour, ram-headed with the 100-grain weight of 34 g. Wider-canopy spread with semi-erect to semi-spread growth habit, bold grains, higher grain yield, resistance to fusariumoxysporum and moderately resistance to ascochytarabiei are its salient characteristics. This article concludes that the art of conventional plant breeding still leads the modern era of biotechnology in crop varietal development with desirable traits.
Keywords: Chickpea kabuli; yield potential; bold seed; fusarium wilt; ascochyta blight